Comparison of Pipeline Embolization Device and Traditional Endovascular Therapeutic Approaches in Distal Cerebral Circulation Aneurysms Using Propensity Score Matching Analysis - Chao Ma; Chao Ma; Haoyu Zhu; Shikai Liang; Fei Liang; Jidian Sun; Yupeng Zhang; Chuhan Jiang (Frontiers in Neurology, 2022)
BackgroundCoiling and stent-assisted coiling remain the first-line treatments for distal cerebral circulation aneurysms (DCCAs). The off-label use of the pipeline embolization device (PED) for these aneurysms has been explored recently but remains controversial.ObjectiveTo compare traditional endovascular therapeutic approaches (coiling and stent-assisted coiling) and PED for DCCAs in a multicenter cohort of patients.MethodsA multicenter, retrospective cohort comparison study was conducted that included consecutive patients with unruptured DCCAs treated with either traditional endovascular therapeutic approaches or PED placement at three centers between 2016 and 2020. Propensity score matching analysis was applied to adjust for baseline risk factors between the PED and TET groups. Matching was based on age, sex, aneurysm size, location, morphology, adjunctive coiling, treatment history, and preoperative mRS score.ResultsIn total, 209 patients with DCCAs treated with PED or traditional endovascular therapeutic approaches were identified. Thirty-seven patients underwent PED treatment, and 172 patients underwent traditional endovascular therapeutic approaches. After propensity score matching, 37 aneurysm pairs were matched, and the baseline characteristics of the patients were balanced between the groups. The complete occlusion rate between PED and traditional endovascular therapeutic approach in both matched cohorts (91.7 vs. 92.3%, p > 0.78) was similar. The rate of periprocedural treatment-related complications in both the PED and traditional endovascular therapeutic groups was 13.5%. Univariate analysis identified average parent vessel diameter as the only predictor of complete occlusion (p = 0.038).ConclusionsPED is a viable option for treating DCCAs by providing occlusion and complication rates similar to those of traditional endovascular therapeutic approaches. A rigid patient selection procedure and proper planning should be undertaken to reduce treatment-related complications.